Estructura horizontal de especies comerciales del bosque de colina baja de la concesión forestal 16-lor-mar/com-mad 2016-049, distrito de Pebas-Yavari, Loreto. 2022 - Salazar Sosa, Rafael Fernando (2024)
In the lowland hill forest of forest concession 16-LOR-MAR/COM-MAD-2016-049, located in the district of Pebas, Yavarí (Loreto), a total of 347 trees were recorded. These data were obtained from the PC1 forest census conducted for timber production purposes, allowing for an assessment of the horizontal structure of the commercial species. The trees were grouped into nine species distributed across seven botanical families, with Fabaceae and Myristicaceae representing the families with the greatest diversity, each comprising two species. The distribution of tree numbers per diameter class reached 1.37 trees per hectare. Notable species included Iryanthera grandis (0.41 trees/ha, 104 trees), Macrolobium gracile (0.28 trees/ha, 72 trees), Otoba parvifolia (0.21 trees/ha, 52 trees), and Carapa procera (0.14 trees/ha, 35 trees). Ecologically, Iryanthera grandis (Myristicaceae) was the most significant, with an Importance Value Index (IVI) of 65.16%, followed by Macrolobium gracile (58.17%), Otoba parvifolia (42.30%), Cedrelinga cateniformis (29.16%), and Carapa procera (28.60%). Finally, the results indicate highly significant differences in the averages of horizontal structure among species.